NALAR KRITIS TERHADAP KONSEP KAFA’AH DALAM HUKUM KELUARGA ISLAM - Edi Susilo (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
One of the goals of kafa'ah is to avoid negative impacts on married couples who are considered unequal. However, equality has a destructive impact because sometimes equality is precisely to differentiate between caste, rank, nobility and seems to be degrading. It is contrary to the principles of Islamic law. This research aims to examine the existence of kafa'ah critically and then reconceptualize the equality of marriage that is free from the social class system. Library research is selected by referring to various sources of books, journals, and other sources to explore the concept of kafa'ah. The research findings show that household equality that is not based on religion is merely sociological and seems to construct a caste and degree comparison, even to the point of degrading, contrary to the principles in Islamic law. So the concept of equality needs to be studied critically and deeply.